Transitions to Professional Nursing Practice - Murphy, Jamie (Open textbook library., 2020)
Transitions to Professional Nursing Practice provides a pivotal learning experience for students transitioning from an associate degree education to a baccalaureate degree. Content includes a broad overview of the nursing profession, the role of accrediting and professional organizations with a strong focus on the American Nurses Association’s foundational documents. The competencies of the Standards of Professional Practice and the Code of Ethics are weaved throughout the text. Topics covered in this text include professional nursing practice, baccalaureate education, healthcare in the 21st century, autonomy and accountability, nursing philosophy, professional development, communication, interprofessional collaboration, critical thinking, introduction to evidence-based practice, and nursing leadership and theory.